2018
DOI: 10.5851/kosfa.2018.e32
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactobacillus helveticus Fermentation on the Ca2+ Release and Antioxidative Properties of Sheep Bone Hydrolysate

Abstract: Both the calcium and collagen in bone powder are hard to be absorbed by the body. Although enzymatic hydrolysis by protease increased the bio-availability of bone powder, it was a meaningful try to further increase Ca2+ release, oligopeptide formation and antioxidant activity of the sheep bone hydrolysate (SBH) by lactic acid bacteria (LAB) fermentation. Lactobacillus helveticus was selected as the starter for its highest protease-producing ability among 5 tested LAB strains. The content of liberated Ca2+ was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
(25 reference statements)
2
7
0
Order By: Relevance
“…Studies have shown that this probiotic lowers serum cholesterol and triglyceride levels [18,19]. Lactobacillus plantarum ST-III promotes intracellular Ca 2 + assimilation at the cellular level to reduce ERS caused by liver injury [20][21][22]. Therefore, in the present study, we investigated the effects of Lactobacillus plantarum ST-III culture supernatants (L-P-cs) in a mice model of CCl 4 -induced liver injury.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that this probiotic lowers serum cholesterol and triglyceride levels [18,19]. Lactobacillus plantarum ST-III promotes intracellular Ca 2 + assimilation at the cellular level to reduce ERS caused by liver injury [20][21][22]. Therefore, in the present study, we investigated the effects of Lactobacillus plantarum ST-III culture supernatants (L-P-cs) in a mice model of CCl 4 -induced liver injury.…”
Section: Introductionmentioning
confidence: 99%
“…Starch was the least effective in this regard and conferred a DH of only 1.29%. This result was consistent with a previous report indicating that glucose, lactose, and fructose could be effectively metabolized by L. helveticus strains 28 and glucose was the most favorable for supporting their proteolytic activity 29 . The lower effectiveness of starch might be ascribed to the poor amylolytic activity of the strain used.…”
Section: Resultssupporting
confidence: 93%
“…The LPP content in the hydrolysate was positively related to the DH of CGM; that is, the highest LPP content of 369.1 mg kg −1 occurred in 20 g kg −1 glucose and the lowest value of 70.7 mg kg −1 was seen in 50 g kg −1 glucose. Such a great difference between the maximum and minimum LPP content compared with that of DH implied that the glucose concentration could possibly affect the proteolytic enzyme profile of the strain, 29 which affected the release of LPP from CGM; or LPP was preferably consumed by the bacteria in the case of nitrogen starvation caused by high glucose concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, reductones formed during fermentation could react with free radicals to stabilize and terminate radical chain reactions [33]. is could explain different results previously obtained for the antioxidant properties of fermented milk of different sources which greatly depend on several factors including the food matrix composition, overall peptidic profile, amino acid composition of the individual peptide, and the large differences between species or even strains used in fermentation [34].…”
Section: Resultsmentioning
confidence: 99%